Biocompatibility and Surface Properties of TiO(2) Thin Films Deposited by DC Magnetron Sputtering - López-Huerta, Francisco (Materials (Basel), 2014)
We present the study of the biocompatibility and surface properties of titanium dioxide (TiO(2)) thin films deposited by direct current magnetron sputtering. These films are deposited on a quartz substrate at room temperature and annealed with different temperatures (100, 300, 500, 800 and 1100 °C). The biocompatibility of the TiO(2) thin films is analyzed using primary cultures of dorsal root ganglion (DRG) of Wistar rats, whose neurons are incubated on the TiO(2) thin films and on a control substrate during 18 to 24 h. These neurons are activated by electrical stimuli and its ionic currents and action potential activity recorded. Through X-ray diffraction (XRD), the surface of TiO(2) thin films showed a good quality, homogeneity and roughness. The XRD results showed the anatase to rutile phase transition in TiO(2) thin films at temperatures between 500 and 1100 °C. This phase had a grain size from 15 to 38 nm, which allowed a suitable structural and crystal phase stability of the TiO(2) thin films for low and high temperature. The biocompatibility experiments of these films indicated that they were appropriated for culture of living neurons which displayed normal electrical behavior.